PHYSICOCHEMISTRY ANALYSIS OF BLACK RICE FLOUR AND ORGANOLEPTIC TESTS OF COOKIES BLACK RICE FLOUR AND WHITE RICE FLOUR - Purwanti, Yunika; Unzilatirrizqi, Yan El Rizal (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2022)
The demand for wheat flour in Indonesia is very high, even though local food ingredients have the potential to be applied in food processing. The alternative is to use local food ingredients that have high nutritional content, through food diversification, it will support the national food security program and reduce people's dependence on flour. Local food ingredients include rice, which is further processed into rice flour. This study aims to determine the physicochemical characteristics of sirampog black rice flour and to determine the response of panelists to white rice and black rice cookies. The design used was a randomized block design (RAK) with 1 factor (type of flour) and 2 levels (white rice flour and black rice flour). The number of treatments was 2 with 5 repetitions. The research analysis was a test of physicochemical characteristics and a preference test which included texture, aroma, taste, and overall acceptance which was then carried out by a T test. The results of the research on the physicochemical characteristics of sirampog black rice flour had a yield of 98%, water absorption capacity of 44.8%, density of kamba 0.74g/ml, water content 14.44%, ash content 2.76%, fat 3.25%, protein 13.28%, carbohydrates 66.27, total phenol 587.79 mg/100g, and IC 50 16,748 mg/gram. White rice cookies have a very favorable response from the panelists on the overall sensory characteristics which include texture, aroma, taste, acceptance. Meanwhile, black rice cookies have a response from panelists who like the texture preference test, like the aroma preference test and overall acceptance, and really like the taste preference test. Keywords: physicochemistry, preference test, cookies, black rice flour